In-plane magnetic anisotropy of the Sr4Ru3O10 nanosheet probed by planar Hall effect - Liu, Yan; Yang, Jiyong; Chu, Weiwei; Du, Haifeng; Ning, Wei; Ling, Langsheng; Tong, Wei; Qu, Zhe; Cao, Gang; Zhang, Yuheng; Tian, Mingliang (Applied physics letters, 2017)
The planar Hall effect (PHE) in a ruthenate Sr4Ru3O10 nanosheet as a function of the magnetic field direction and temperature has been investigated. From the magnetic reversal induced PHE signal, we find that the [ 1 ¯ 10] direction is the in-plane ferromagnetic easy-axis and the [110] direction is a metastable magnetic axis of the Sr4Ru3O10 nanosheet. This in-plane magnetic anisotropy can lead to a large, measurable, and field direction sensitive resistance switching when an in-plane magnetic field is swept, suggesting that Sr4Ru3O10 may have potential applications in spintronic and magnetic sensor devices.